Optimization of formula sustained releaase captopril tablet using factorial design method - Pratiwi, Melinda; Hadisoewignyo, Lannie (Indonesian Journal of Pharmacy, 2010)
Captopril is one of the most frequently used  medicine  in the treatment of hypertension  with  repeatedly  used  frequency  in  a  day.  Therefore  captopril should  be  formulated  in  the  form  of  sustained  release  and  find  the  optimum formula.  The  purpose  of  this  study  was  to  determine  the  influence  of  both factors  and  their  interactions,  which  are  the  ratio  of  polymer  HPMC  K4M  -xanthan gum  factor at the level of 1:1 and 4:1 and the concentration of tartaric acid  at  levels  of  0%  and  5%  on  physical  properties  of  tablets,  drug  release, floating  lag  time.  Furthermore,  find  the  optimum  formula  that  meets  the requirements  and  produce  tablets  with  drug  release  pattern  according  to  zero order  kinetics.  Based  on  Design  Expert  optimization  program  was  obtained  the optimum  formula  using  a  combination  of  polymer  HPMC  K4M  –  xanthan  gum ratio  3.75:1  and  concentration  of  of  tartaric  acid  4.5%  would  be  result  the hardness  respons  12.02  Kp  the  friability  0.47%,  the  floating  lag  time  0.32 minutes,  and  the  rate  of  dissolution  0.05  mg/min.  The  results  show  that combination of factors polymer HPMC K4M -  xanthan gum ratio can increase the tablet  hardness,  lower  tablet  friability,  accelerate  the  floating  lag  time,  and increase the rate  of dissolution.  Tartaric acid can  decrease  the  tablet  hardness, increase  the  friability,  accelerate  the  floating  lag  time,  and  increase   the  rate  of dissolution.  Interaction  of  both  can  reduce  the  tablet  hardness,  increase  the tablet friability, slow floating lag time, and increase the rate of dissolution.Key words: captopril, HPMC K4M, xanthan gum, tartaric acid, factorial design